Identifying teaching best practices for accounting courses using appreciative inquiry. (2017) - Brands, Kristine M.; Elam, Debora
Eagle Mountain University (EMU) recently merged its two separate accounting programs into a new college. While the transition from two programs to one program involves many challenges, a priority is the alignment of teaching best practices for accounting courses. This study addresses that objective. An earlier study by the researchers examined quality enablers for online accounting programs by examining a small graduate accounting program at a private university in the Western USA. This study performed additional research on this topic by focusing on identifying teaching best practices for accounting courses for the university. The research model used for this project was based on Thatchenkery's appreciative sharing of knowledge (ASK) model because it encourages knowledge sharing to build on the positive experiences of the organisation. This study was conducted using a virtual approach instead of the traditional face-face meetings used by Thatchenkery's ASK model (2005). Based on the findings of the study, a best practices framework for teaching accounting courses was started for EMU.